Retrospective study on the cumulative incidence of milk fever in parturient cows: a case study in the United Arab Emirates - Shaikha Ahmed Alshehhi; Temesgen Mohammed; Aboma Zewude; Berecha Bayissa; Asha Antony; Berhanu Adnew Degafa; Gobena Ameni (BMC Veterinary Research)
Abstract Background Dairy productivity can be improved by controlling metabolic diseases in dairy cows such as milk fever. The aim of this study was to estimate the cumulative incidence of milk fever during four years (2019 to 2022) at an anonymous dairy farm in the Emirate of Abu Dhabi. For this study, the records of the diagnosis of milk fever in 7540 parturient cows during four years was used. Results The monthly cumulative incidence of milk fever over four years was 2.2% (95% confidence interval, CI: 1.9, 2.3%). It was highest in 2021 (3.41 ± 0.41%) while it was lowest (0.87 ± 0.20%) in 2022. Based on multivariate binary logistic regression analysis, the odds of the monthly cumulative incidence of milk fever was 4.12 (95% CI: 2.31, 7.34) times higher in 2021 than in 2022. Similarly, it was 4.30 (95% CI: 2.38, 7.78) times higher in winter than in autumn. On the other hand, the monthly cumulative incidence of milk fever was 0.07 (95% CI: 0.03, 0.16) and 0.41 (95% CI: 0.06, 0.33) times lower in lactations 2 and 3 than in lactation 7, respectively. Lastly, milk fever was significantly associated with subclinical ketosis (χ2 = 54.74; p < 0.001). Conclusion The monthly cumulative incidence of milk fever could be considered as low while further strengthening preventive measures would benefit the farm.